2009
DOI: 10.2174/1876973x00902010119
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Vegetable De Oiled Cake-Diesel Blends on Diesel Engine

Abstract: Alternative sources for petroleum fuels have been the prime concern of most of the environmentalists. It is also a concern for economists due to the depletable nature of the fossil fuel. Vegetable oils are considered as good alternatives to diesel as their properties are close to diesel. At present biodiesel is commercially produced from the vegetable oils by esterification processes. Since most of these oils are edible, its cost restricts the usage. The de oiled cakes after crushing the seeds contains around … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2010
2010

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…The stoichiometric air requirement for the combustion of additives is lower, since they already contain oxygen in their structure, hence a larger amount of fuel can be burnt in a given amount of air and hence the BSFC decreases for the blends compared with baseline fuel (Raj et al, 2009a) as shown in Figure 2. From the figure it is observed that the addition of PN reduce the BSFC due to the availability of more oxygen.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The stoichiometric air requirement for the combustion of additives is lower, since they already contain oxygen in their structure, hence a larger amount of fuel can be burnt in a given amount of air and hence the BSFC decreases for the blends compared with baseline fuel (Raj et al, 2009a) as shown in Figure 2. From the figure it is observed that the addition of PN reduce the BSFC due to the availability of more oxygen.…”
Section: Resultsmentioning
confidence: 99%
“…Mohanan et al (2003) studied the effect of DEE on the performance and emissions of a four-stroke direct injection diesel engine and found that 5% DEE can be blended with diesel fuel to improve the performance and to reduce emissions of the diesel engine even though experiments were carried out successfully up to 25% DEE blend. Yanfeng et al (2007) proved 15% of 2-methoxyethyl acetate (MEA) can be used to decrease exhaust smoke as a new oxygenated additive of diesel with marginal increase in efficiency Raj et al (2009a) investigated the effect of ethanol diesel blends and reported 30% ethanol with 60% diesel along with a new oxygenate 1,4 dioxane increase the efficiency by 6% and reduce smoke density with a penalty in NOx emissions. Raj et al (2009b) also found that 10% addition of dioxane alone as an oxygenated additive is capable of increasing the efficiency by 2% and reduces smoke density with marginal increase in NOx emissions.…”
Section: Introductionmentioning
confidence: 99%